Spatial imagery relies on a sensory independent, though sensory sensitive, functional organization within the parietal cortex: A fMRI study of angle discrimination in sighted and congenitally blind individuals. (February 2015) - Bonino, Daniela; Ricciardi, Emiliano; Bernardi, Giulio; Sani, Lorenzo; Gentili, Claudio; Vecchi, Tomaso; Pietrini, Pietro
Abstract: Although vision offers distinctive information to space representation, individuals who lack vision since birth often show perceptual and representational skills comparable to those found in sighted individuals. However, congenitally blind individuals may result in impaired spatial analysis, when engaging in 'visual' spatial features (e.g., perspective or angle representation) or complex spatial mental abilities. In the present study, we measured behavioral and brain responses using functional magnetic resonance imaging in sighted and congenitally blind individuals during spatial imagery based on a modified version of the mental clock task (e.g., angle discrimination) and a simple recognition control condition, as conveyed across distinct sensory modalities: visual (sighted individuals only), tactile and auditory. Blind individuals were significantly less accurate during the auditory task, but comparable-to-sighted during the tactile task. As expected, both groups showed common neural activations in intraparietal and superior parietal regions across visual and non-visual spatial perception and imagery conditions, indicating the more abstract, sensory independent functional organization of these cortical areas, a property that we named supramodality . At the same time, however, comparisons in brain responses and functional connectivity patterns across experimental conditions demonstrated also a functional lateralization, in a way that correlated with the distinct behavioral performance in blind and sighted individuals. Specifically, blind individuals relied more on right parietal regions, mainly in the tactile and less in the auditory spatial processing. In sighted, spatial representation across modalities relied more on left parietal regions. In conclusions, intraparietal and superior parietal regions subserve supramodal spatial representations in sighted and congenitally blind individuals. Differences in their recruitment across non-visual spatial processing in sighted and blind individuals may be related to distinctive behavioral performance and/or mental strategies adopted when they deal with the same spatial representation as conveyed through different sensory modalities. Highlights: Supramodal spatial representations activate parietal cortex in sighted and blind individuals. Auditory, but not tactile, angle discrimination is impaired in early blinds. Blinds rely more on right parietal cortex, mainly during tactile spatial processing. Sighted rely more on left parietal cortex across sensory modalities. Parietal lateralization may reflect distinct mental representations/strategies.